2023
DOI: 10.1088/2632-2153/acd168
|View full text |Cite
|
Sign up to set email alerts
|

Applications of physics informed neural operators

Abstract: We present a critical analysis of physics-informed neural operators to solve partial differential equations that are ubiquitous in the study and modeling of physics phenomena using carefully curated datasets. Further, we provide a benchmarking suite which can be used to evaluate physics-informed neural operators in solving such problems. We first demonstrate that our methods reproduce the accuracy and performance of other neural operators published elsewhere in the literature to learn the 1D wave equation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…These studies shed new light into the features and patterns that AI extracts from data to make reliable predictions. Similarly, recent studies 52 – 54 have demonstrated that incorporating domain knowledge in the architecture of AI models, and optimization methods (through geometric deep learning and domain aware loss functions) leads to faster (even zero shot) learning and convergence, and optimal performance with smaller training and validation datasets.…”
Section: Fair Initiativesmentioning
confidence: 91%
“…These studies shed new light into the features and patterns that AI extracts from data to make reliable predictions. Similarly, recent studies 52 – 54 have demonstrated that incorporating domain knowledge in the architecture of AI models, and optimization methods (through geometric deep learning and domain aware loss functions) leads to faster (even zero shot) learning and convergence, and optimal performance with smaller training and validation datasets.…”
Section: Fair Initiativesmentioning
confidence: 91%
“…Here, the number of input channels of FNO is increased to consider more parameters related to landslide dynamics, especially introducing terrain so that the model can be used in real scenarios. We use the Adam optimizer (Bock & Weiß, 2019; Sun, 2020) with the relative mean square error (MSE) loss function (Rosofsky et al., 2023) to calculate the loss value during model training, taking into account the relative variations of the datasets. Nonlinear transformations are achieved using the Gelu activation function.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, FNO showcases super‐resolution prowess, permitting training on low‐resolution data while delivering high‐resolution results devoid of accuracy loss (Lu et al., 2021). The FNO‐based neural network paradigm has found successful applications across diverse domains, yielding outstanding performance (Guan et al., 2023; Rosofsky et al., 2023; Wen et al., 2022; You et al., 2022). Nevertheless, to date, there exists a conspicuous paucity of endeavors employing FNO‐based methodologies to address real‐world dynamic processes (especially landslide dynamics).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of data-scarcity arising from the profound computational intensiveness of 3D simulations could also be combat by using physics-informed models, where the information regarding the PDE is hard-baked into the model architecture or the training regime. Recent works on physics informed neural operators has shown promise in fine-tuning coarsely trained models with PDE constraints within MHD scenarios [44].…”
Section: Scaling To 3dmentioning
confidence: 99%